EMPOWER: An Online Staff Training Focused on Person-Centered Supports for Direct Support Professionals - Amy Castagnino; Meghan Blaskowitz (Scholarworks @ WMU, 2022)
Background: Direct support professionals (DSPs) for individuals with intellectual and developmental disabilities (IDD) is one of the most rapidly growing professions in the United States. However, there is a gap in recruiting, training, and retraining DSPs to provide appropriate and effective person-centered supports. Method: The aim of this pilot study was to measure the effectiveness of a staff training program conducted by an occupational therapy doctoral candidate, focused on improving DSPs' confidence and competence when providing services to adults with IDD. A pretest/posttest quantitative design was used to test changes in the DSPs' confidence from the beginning to end of the training and competence from the beginning to end of each weekly module. Results: As a result of the training, the DSPs improved both their confidence and competence in providing person-centered supports with statistically significant (with Bonferroni correction applied) and positive clinical outcomes (reported Cohen's d large effect). Conclusions: While preliminary, this study shows that training programs for DSPs implemented through an occupational therapy lens have the potential to improve the confidence and competence of DSPs for providing person-centered supports for individuals with intellectual and developmental disabilities.